2002
DOI: 10.4049/jimmunol.169.3.1556
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the IFN-γ-Inducible CXCR3-Binding Chemokines, IFN-Inducible Protein 10, Monokine Induced by IFN, and IFN-Inducible T Cell α Chemoattractant in Human Cardiac Allografts: Association with Cardiac Allograft Vasculopathy and Acute Rejection

Abstract: CXCR3 chemokines exert potent biological effects on both immune and vascular cells. The dual targets suggest their important roles in cardiac allograft vasculopathy (CAV) and rejection. Therefore, we investigated expression of IFN-inducible protein 10 (IP-10), IFN-inducible T cell α chemoattractant (I-TAC), monokine induced by IFN (Mig), and their receptor CXCR3 in consecutive endomyocardial biopsies (n = 133) from human cardiac allografts and corresponding normal donor hearts (n = 11) before transplantation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(145 citation statements)
references
References 26 publications
7
138
0
Order By: Relevance
“…It is noteworthy that just as CXCL10 and CXCL11 were, and CXCL9 was not, induced by infection with HIV-1 in vitro, CXCL10 and CXCL11 were expressed in an identical pattern in vivo, which differed from the pattern that we saw for CXCL9 (36). These observations are analogous to those by Zhao et al (58), who reported that CXCL10 and CXCL11 were both expressed by vessels in endomyocardial biopsies from human cardiac allografts, which was not the case for CXCL9. To our knowledge, our study is the first demonstration of the expression of chemokines by venules of HIV-1-infected lymph node, providing candidates mediating the enhanced recruitment of T cells to these tissues.…”
Section: Figuresupporting
confidence: 58%
“…It is noteworthy that just as CXCL10 and CXCL11 were, and CXCL9 was not, induced by infection with HIV-1 in vitro, CXCL10 and CXCL11 were expressed in an identical pattern in vivo, which differed from the pattern that we saw for CXCL9 (36). These observations are analogous to those by Zhao et al (58), who reported that CXCL10 and CXCL11 were both expressed by vessels in endomyocardial biopsies from human cardiac allografts, which was not the case for CXCL9. To our knowledge, our study is the first demonstration of the expression of chemokines by venules of HIV-1-infected lymph node, providing candidates mediating the enhanced recruitment of T cells to these tissues.…”
Section: Figuresupporting
confidence: 58%
“…They also found that, treatment of recipients with KC antiserum at the time of transplant subsequently decreases intragraft expression of the activated T-cell chemoattractants IP-10 (CXCL10) and MIG (CXCL9). As IP-10 and MIG can play essential roles in allograft rejection (18,19,23,24), these reports demonstrate that innate immune components can have profound effects on subsequent alloantigen-specific rejection. Our data show the induction of this cascade in the transplanted hearts and identify potential candidates that may be antagonized to attenuate rejection of cardiac allografts.…”
Section: Discussionmentioning
confidence: 80%
“…Although a number of clinical investigations focused on other putative indicators of alloreaction like IL-2, MCP-1, or granzyme B (27)(28)(29), more recently transplantation studies in animals (8,24,30) and measurements of chemokine mRNA in biopsy specimens (11,12,31,32) have stressed the prominent role of IFN-␥-dependent chemokines, especially MIG, for the acute phase of allograft rejection. Urinary measurements of MIG in a small number of pediatric patients (33) and in adult renal allograft patients support our data (34,35).…”
Section: Discussionmentioning
confidence: 99%